Impact of Armed Conflict on Socio-economic Development in the Democratic Republic of Congo: Strategies for Sustainable Economic Development - Mashala Bitwakamba, Grégoire; Meyi Marcel, Bwama; Ciminello, Romeo (European Journal of Sustainable Development, 2018)
The present study is an analysis of the complex causes of recent and past conflicts in the DRC and their multiple effects on socio-economic development. It examines the impact of conflict on the macroeconomic, sectoral sectors, natural resources and finally on social and human development. The goal is to take on the root causes of conflict in order to establish a solid foundation for sustainable economic development. As a method, the study takes a historical perspective to identify common factors of past and present conflicts. It analyzes quantitatively and qualitatively the root causes of conflicts in the DRC to detect their impact on various aspects of economic and social development at national and regional level and to propose strategies to restore subsistence sustainable supports, economic and social development in the DRC. In addition to the introduction, the study presents four main points: the geography of the DRC, the causes of conflict, the impact of conflict and strategies for sustainable economic and human development. Keywords: Armed conflicts ; socio-economic’s development ; human and development trategies in RDC